The new pie : modern techniques for the classic American dessert - Taylor, Chris, 1968 August 13-; Arguin, Paul M (Clarkson Potter/Publishers, 2019)
Get ready for a new, fresh take on baking the ultimate feel-good dessert: pie! In The New Pie, Chris Taylor and Paul Arguin--winners of more than 500 awards for baking (including the 2017 Best of Show Award at the National Pie Championships)--re-examine the wholesome world of pie. Through traditional time-honored techniques, modern cooking methods (like sous vide), innovative flavors (birthday cake; Tahitian pineapple; and mocha "mystery"), and a love for kitchen gadgets (like immersion circulators and silicone texture mats), these legendary competition circuit pie experts reinvent the traditional pastime of pie-making. With step-by-step instructions and playful photography, you'll learn to make groundbreaking creations, including a magnificent Blueberry-Maple Pie with wood-grain lattice, the King Fluffernutter Pie, and a striped chocolate Pie of the Tiger. Whether you are a pie voyeur, new baker, or baking enthusiast you will find inspiration at every turn and pies to satisfy every craving.